2017
DOI: 10.1101/180612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into regeneration from the genome, transcriptome and metagenome analysis ofEisenia fetida

Abstract: Earthworms show a wide spectrum of regenerative potential with certain species like Eisenia fetida capable of regenerating more than two-thirds of their body while other closely related species, such as Paranais litoralis seem to have lost this ability. Earthworms belong to the phylum annelida, in which the genomes of the marine oligochaete Capitella telata, and the freshwater leech Helobdella robusta have been sequenced and studied. The terrestrial annelids, in spite of their ecological relevance and unique b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 98 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Emerging genomic methods will be useful to understand this process. By sequencing genomes and transcriptomes, genes involved in regeneration can be identified (Bhambri et al, 2017;Myohara et al, 2006;Nyberg et al, 2012), thereby opening up the possibility of a functional characterization, e.g., by CRISPR or RNAi methods (Boettcher & McManus, 2015). Different studies of annelid regeneration identified the expression of genes such as engrailed, wingless (Wnt), orthodenticle homologs, markers of germline cells (e.g.…”
Section: Reports Of Bifurcated Patterns In Regeneration Are Known Frommentioning
confidence: 99%
“…Emerging genomic methods will be useful to understand this process. By sequencing genomes and transcriptomes, genes involved in regeneration can be identified (Bhambri et al, 2017;Myohara et al, 2006;Nyberg et al, 2012), thereby opening up the possibility of a functional characterization, e.g., by CRISPR or RNAi methods (Boettcher & McManus, 2015). Different studies of annelid regeneration identified the expression of genes such as engrailed, wingless (Wnt), orthodenticle homologs, markers of germline cells (e.g.…”
Section: Reports Of Bifurcated Patterns In Regeneration Are Known Frommentioning
confidence: 99%